Design and Analysis of a Novel Compact Wideband Antenna with Two Excited Modes - Li Li; Zhi-Li Zhou; Jing-Song Hong (International Journal of Antennas and Propagation)
A novel planar compact wideband antenna with coplanar waveguide (CPW) feeding configuration is presented in this paper. The proposed antenna is fed and coupled by the CPW feeding line at the same time. Therefore, two distinct excited modes are realized. Besides, detail investigation is presented as well to demonstrate the properties of the proposed antenna. Eventually, the prototype of the proposed antenna with optimal design is fabricated and tested. The proposed antenna, with a fairly compact size of 24 mm × 18 mm × 1 mm, has a measured 10 dB impedance bandwidth spanning from 3.05 GHz to 6 GHz, about 65.2%. Moreover, stable radiation patterns over the operating band are obtained. Furthermore, time-domain characteristics of the proposed antenna are also investigated.